THE CONCEPT OF ANTI CORRUPTION RELIGIOUS EDUCATION IN BASIC SCHOOL - Abdulloh Hadziq (Elementary: Islamic Teacher Journal, 2017)
The phenomenon of the ineffectiveness of the role of religion in building a clean society from corruption must be realized together. Therefore, Islamic education is expected to be a solution in dealing with corruption now and in the future, especially in the early preventive efforts. The theoretical approach of religion-based anti-corruption education seeks to see the extent to which the reality of society can be accommodated in aspects of Anti-Corruption Education, both on material aspects, learning methods, means of infrastructure and so forth. Islamic education in schools can play a role in combating corruption by integrating contextual Islamic learning materials with messages to be conveyed with regard to corruption. The research design used was qualitative which focused on anti-corruption religious education in elementary school. If this concept is applied, it is expected to change in the mindset of learners of religious values that can be applied in empirical life. So that further impact towards the realization of quality and dignified Indonesian society.